A Rat Model of Alzheimer’s Disease Based on Abeta42 and Pro-oxidative Substances Exhibits Cognitive Deficit and Alterations in Glutamatergic and Cholinergic Neurotransmitter Systems - Petrasek, Tomas; Skurlova, Martina; Maleninska, Kristyna; Vojtechova, Iveta; Kristofikova, Zdena; Matuskova, Hana; Sirova, Jana; Vales, Karel; Ripova, Daniela; Stuchlik, Ales (Frontiers in Aging Neuroscience, 2016)
Alzheimer´s disease (AD) is one of the most serious human, medical, and socioeconomic burdens. Here we tested the hypothesis that a rat model of Alzheimer´s disease (Samaritan; Taconic Pharmaceuticals, USA) based on the application of amyloid beta42 and the pro-oxidative substances ferrous sulfate heptahydrate and L-buthionine-(S,R)-sulfoximine, will exhibit cognitive deficits and disruption of the glutamatergic and cholinergic systems in the brain. Behavioral methods included the Morris water maze (long-term memory version) and the active allothetic place avoidance task (acquisition and reversal), testing spatial memory and different aspects of hippocampal function. Neurochemical methods included testing of the NR1/NR2A/NR2B subunits of NMDA receptors in the frontal cortex and CHT1 transporters in the hippocampus, in both cases in the right and left hemisphere separately. Our results show that Samaritan rats™ exhibit marked impairment in both the Morris water maze and active place avoidance tasks, suggesting a deficit of spatial learning and memory. Moreover, Samaritan rats exhibited significant changes in NR2A expression and CHT1 activity compared to controls rats, mimicking the situation in patients with early stage AD. Taken together, our results corroborate the hypothesis that Samaritan rats are a promising model of AD in its early stages.